A case of 46, XY disorders of sex development with congenital heart disease caused by a GATA4 variant. (6th July 2022) - Shichiri, Yui; Kato, Yoshimi; Inagaki, Hidehito; Kato, Takema; Ishihara, Naoko; Miyata, Masafumi; Boda, Hiroko; Kojima, Arisa; Miyake, Misa; Kurahashi, Hiroki
Abstract: GATA4 is known to be a causative gene for congenital heart disease, but has also now been associated with disorders of sexual development (DSD). We here report a pathogenic variant of GATA4 in a 46, XY DSD patient with an atrial septal defect, identified by whole‐exome sequencing to be c.487C>T (p.Pro163Ser). This mutation resulted in reduced transcriptional activity of the downstream gene. When we compared this transcriptional activity level with other GATA4 variants, those that had been identified in patients with cardiac defects and DSD showed less activity than those in patients with cardiac defect only. This suggests that the normal development of the heart requires more strict regulation of GATA4 transcription than testicular development. Further, when the different variants were co‐expressed with wild‐type, the transcriptional activities were consistently lower than would be expected from an additive effect, suggesting a dominant‐negative impact of the variant via dimer formation of the GATA4 protein. Since these pathogenic GATA4 variants are occasionally identified in healthy parents, a threshold model of quantitative traits may explain the cardiac defect or DSD phenotypes that they cause.